Wacana Rasisme: Bentuk Rasisme dalam Series Anime One Piece - Ilham Muhammad Akbar; Sumaina Duku; Lilis Sukmawati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study is entitled "Racism Discourse: Racial Discrimination and Social Inequality in the Anime Series One Piece." The research is motivated by the depiction of various forms of racism and social inequality presented through inter-racial conflicts in the anime. Issues of racism are reflected in acts of oppression, slavery, injustice, and unequal treatment. This anime was chosen because it portrays social realities related to power relations and discrimination that continue to exist in society. The purpose of this study is to analyze the forms of racism and social inequality represented in the anime. This research employs a qualitative descriptive approach. The data consist of scenes, dialogues, and storylines related to acts of racism and social inequality. Data collection was conducted through documentation techniques by observing and recording scenes relevant to the focus of the study. The analysis uses Norman Fairclough’s Critical Discourse Analysis theory, which divides discourse analysis into three dimensions: textual dimension, discursive practice dimension, and social practice dimension. The findings indicate the presence of various forms of racism and social inequality influenced by power relations within the narrative. In addition, the study identifies interpersonal conflicts, intergroup conflicts, and structural conflicts that demonstrate the domination of certain groups over those considered inferior. The results reveal that anime functions not only as a form of entertainment but also as a medium for conveying social criticism regarding the realities of racism and social inequality in society